Natural Excipients: Role in Nano Drug Delivery System - Jirvankar, Pranita; Agrawal, Surendra; Shaikh, Fuzail; Borse, Kadambari (Current Nanomaterials, 2025)
BackgroundExcipients are increasingly employed in novel dosage forms to accomplish specialized roles, and they also directly or indirectly alter the extent and rate of drug release and absorption. The trend toward using plant-based and natural goods has raised demand and, in some ways, replaced synthetic additives with natural ones. Natural and semisynthetic materials offer various advantages over synthetic materials since they are chemically inert, less toxic, less expensive, biodegradable, increase product shelf life, and are widely accessible.ObjectivesThis review aims to cover the natural excipients’ role in nanoformulations and associated prospects.MethodsMore than 500 manuscripts were collected from ScienceDirect, PubMed, google, and other sources; however the manuscripts were excluded based on their relevance to the subject and finally 80 manuscripts were analyzed for the data.ResultsThe substation of synthetic lipids with natural and semisynthetic for developing lipid-based nano drug delivery, and the use of gelatin and chitosan in developing encapsulated and nano particulates are a few examples to understand the above-mentioned transition.ConclusionThis review provides an overview of the types of excipients used in the formulation of novel drug delivery systems with special emphasis on their characteristics, safety aspects, benefits associated, and common methods through, which they are employed in nanoformulations.
Keywords: nanoformulations